Towards catchment classification in data‐scarce regions. Issue 7 (29th January 2016) - Auerbach, Daniel A.; Buchanan, Brian P.; Alexiades, Alexander V.; Anderson, Elizabeth P.; Encalada, Andrea C.; Larson, Erin I.; McManamay, Ryan A.; Poe, Gregory L.; Walter, M.Todd; Flecker, Alexander S.
Abstract: Assessing spatial variation in hydrologic processes can help to inform freshwater management and advance ecological understanding, yet many areas lack sufficient flow records on which to base classifications. Seeking to address this challenge, we apply concepts developed in data‐rich settings to public, global data in order to demonstrate a broadly replicable approach to characterizing hydrologic variation. The proposed approach groups the basins associated with reaches in a river network according to key environmental drivers of hydrologic conditions. This initial study examines Colorado (USA), where long‐term streamflow records permit comparison with previously distinguished flow regime types, and Ecuador, where data limitations preclude such analysis. The flow regime types assigned to gages in Colorado corresponded reasonably well to the classes distinguished from environmental features. The divisions in Ecuador reflected major known biophysical gradients while also providing a higher resolution supplement to an existing depiction of freshwater ecoregions. Although freshwater policy and management decisions occur amidst uncertainty and imperfect knowledge, this classification framework offers a rigorous and transferrable means to distinguish catchments in data‐scarce regions. The maps and attributes of the resulting ecohydrologic classes offer a departure point for additional study and data collection programmes such as the placement of stations in under‐monitored classes, and the divisions may serve as a preliminary template with which to structure conservation efforts such as environmental flow assessments. Copyright © 2015 John Wiley & Sons, Ltd.